2012
DOI: 10.1161/circulationaha.111.038919
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and Vascular Oxidation Limits the Efficacy of Oral Tetrahydrobiopterin Treatment in Patients With Coronary Artery Disease

Abstract: Background-The endothelial nitric oxide synthase cofactor tetrahydrobiopterin (BH4) plays a pivotal role in maintaining endothelial function in experimental vascular disease models and in humans. Augmentation of endogenous BH4 levels by oral BH4 treatment has been proposed as a potential therapeutic strategy in vascular disease states. We sought to determine the mechanisms relating exogenous BH4 to human vascular function and to determine oral BH4 pharmacokinetics in both plasma and vascular tissue in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
119
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(124 citation statements)
references
References 34 publications
(34 reference statements)
5
119
0
Order By: Relevance
“…However, BH 4 supplementation alone does not result in complete recovery of NOS-dependent CF, although tandem replenishment including NADPH does (Reyes et al, 2015). A recent clinical study testing the effect of oral BH 4 on endothelial function in patients with coronary artery disease found that systemic and vascular oxidation of BH 4 limited its protective effects (Cunnington et al, 2012). Considering this finding, it is possible that NADPH-dependent reactions that either salvage BH 4 from its reversible oxidation products through dihydrofolate reductase (Bailey and Ayling, 2009) or complete its de novo synthesis through sepiapterin reductase (Gao et al, 2009) are limited in I/R injury, perhaps by diminished cellular NADPH levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, BH 4 supplementation alone does not result in complete recovery of NOS-dependent CF, although tandem replenishment including NADPH does (Reyes et al, 2015). A recent clinical study testing the effect of oral BH 4 on endothelial function in patients with coronary artery disease found that systemic and vascular oxidation of BH 4 limited its protective effects (Cunnington et al, 2012). Considering this finding, it is possible that NADPH-dependent reactions that either salvage BH 4 from its reversible oxidation products through dihydrofolate reductase (Bailey and Ayling, 2009) or complete its de novo synthesis through sepiapterin reductase (Gao et al, 2009) are limited in I/R injury, perhaps by diminished cellular NADPH levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, several clinical investigations, particularly long-term studies, have failed to translate these observations into clinical benefit (e.g., refs. [7][8][9]. The reasons for these discordant findings are variously attributed to an uncoupling of NOS for L-arginine (10), tolerance and induction per se of vascular dysfunction with the organic nitrates (11), and oxidation of tetrahydrobiopterin (9).…”
mentioning
confidence: 99%
“…[7][8][9]. The reasons for these discordant findings are variously attributed to an uncoupling of NOS for L-arginine (10), tolerance and induction per se of vascular dysfunction with the organic nitrates (11), and oxidation of tetrahydrobiopterin (9). These issues suggest that the failure of translation may lie in the failure of effective delivery of NO rather than a lack of efficacy of NO.…”
mentioning
confidence: 99%
“…However, a recent clinical trial demonstrated that in patients with CAD, oral tetrahydrobiopterin treatment failed to improve endothelial function or cardiovascular outcomes, possibly due to autooxidation of the compound (47).…”
mentioning
confidence: 99%